Existence and uniqueness of solution for two one-phase Stefan problems with variable thermal coefficients. (February 2020) - Bollati, Julieta; Natale, María F.; Semitiel, José A.; Tarzia, Domingo A.
Abstract: One dimensional Stefan problems for a semi-infinite material with temperature dependent thermal coefficients are considered. Existence and uniqueness of solution are obtained imposing a Dirichlet, a Neumann or a Robin type condition at fixed face x = 0 . Moreover, it is proved that the solution of the problem with the Robin type condition converges to the solution of the problem with the Dirichlet condition at the fixed face. Computational examples are provided.